Macromol. Chem. Phys. 17/2018. Issue 17 (5th September 2018) - Kasprzak, Christopher R.; Scherzinger, Evan T.; Sarkar, Amrita; Miao, Miranda; Porcincula, Dominique H.; Madriz, Alejandro M.; Pennewell, Zachary M.; Chau, Sophia S.; Fernando, Raymond; Stefik, Morgan; Zhang, Shanju
Abstract : Front Cover : In article1800197, Shanju Zhang and co‐workers demonstrate a lyotropic liquid crystal templating method to prepare polymer‐carbon nanotube composites with ordered microstructures, from a series of quaternary ammonium surfactants via photopolymerization. Both lamellar and gyroid microstructures of composites are obtained from hexagonal mesophases.